The complete Lady Snowblood [videorecording (DVD)] - Kaji, Meiko; Kurosawa, Toshio; Daimon, Masaaki; Koike, Kazuo, 1936-2019; Kamimura, Kazuo (Criterion collection, 2016)
A young woman, trained from childhood as an assassin and hellbent on revenge for her father's murder and her mother's rape, hacks and slashes her way to gory satisfaction. Rampant with inventive violence and spectacularly choreographed swordplay, the influential cult classic Lady Snowblood and set in late nineteenth century Japan, is a bloody, beautiful extravaganza composed of one elegant widescreen composition.